Strategy for Sustainable Use of Mangrove Ecosystem In Coastal Tatengesan, Southeast Minahasa Regency - Pamungkas, Yogo; Paruntu, Carolus Paulus; Rumengan, Antonius Petrus; Manembu, Indri Shelovita; Sondak, Calvyn Fredrik Aldus; Ginting, Elvy Like (Jurnal Ilmiah Platax, 2024)
The mangrove ecosystem area in the coastal area of Tatengesan Village, Pusomaen District, Southeast Minahasa Regency has been developed as a mangrove ecotourism area which has been managed by Village-Owned Enterprises (BUMD) since January 2019 with assistance from the Mandiri Rural National Community Empowerment Program (PNPM) team. The development of this mangrove ecotourism activity was stopped for a moment due to the impact of the COVID-19 pandemic, but currently, COVID-19 cases are considered endemic so this mangrove ecotourism activity will be developed again. This research aims to formulate some strategies for the sustainable use of the mangrove ecosystem on the Tatengesan coast, Southeast Minahasa Regency. This research lasted for 5 months, from September 2022 - February 2023. This research used descriptive qualitative methods with survey technique, i.e., in-depth direct interviews with resource persons (respondents). The formulation of priority strategies (key success factors) was analyzed using S.W.O.T and strategy choice analysis. This research produced 9 (nine) priority strategies as academic texts, which can be recommended to governments related to the marine and fisheries sector as elements of public policy-making officials. Keywords: Tatengesan village, mangrove ecotourism, sustainable use, priority strategies. Abstrak Kawasan ekosistem mangrove di wilayah pesisir Desa Tatengesan, Kecamatan Pusomaen, Kabupaten Minahasa Tenggara dikembangkan sebagai kawasan ekowisata mangrove yang dikelola oleh Badan Usaha Milik Desa (BUMD) sejak Januari 2019 dengan pendampingan oleh tim Program Nasional Pemberdayaan Masyarakat (PNPM) Mandiri Perdesaan.  Kegiatan ekowisata mangrove ini pengembangannya terhenti sejenak dikarenakan adanya dampak pandemi Covid-19, namun saat ini kasus Covid-19 sudah dianggap endemi sehingga kegiatan ekowisata mangrove ini akan dikembangkan kembali.  Tujuan penelitian ini yaitu merumuskan strategi pemanfaatan berkelanjutan ekosistem mangrove ke arah berkelanjutan di pesisir Tatengesan Kabupaten Minahasa Tenggara.  Riset ini berlangsung selama 5 bulan, dari September 2022 - Februari 2023.  Riset ini menggunakan metode kualitatif deskriptif dengan teknik survei, yaitu wawancara langsung secara mendalam (in-depth interview) kepada narasumber (responden).  Perumusan strategi prioritas (faktor kunci keberhasilan) di analisis dengan menggunakan S.W.O.T dan analisis pilihan strategi.  Penelitian ini menghasilkan 9 (sembilan) strategi prioritas sebagai naskah akademik, yang dapat direkomendasikan kepada pemerintah terkait pada sektor kelautan dan perikanan sebagai unsur pejabat pembuat kebijakan publik. Kata kunci: Desa Tatengesan, ekowisata mangrove, pemanfaatan berkelanjutan, strategi prioritas.